Empirical Review of Attitude towards Eco-Friendly Hotels - Gui, Qiongfang; Abdullah, Abdul Rashid (International Journal of Global Economics and Management, 2024)
This paper provides an empirical review of consumer attitudes towards eco-friendly hotels, emphasizing the psychological and behavioral components that influence such preferences. Attitudes towards eco-friendly hotels are shaped by cognitive beliefs about the environmental impact and sustainability of these hotels, affective responses such as feelings of satisfaction or ethical alignment, and behavioral tendencies that lead to actual patronage. The paper synthesizes findings from various studies to illustrate how these attitudes can be significantly shaped by individual beliefs, values, emotional responses, and the perceived benefits of sustainability. It highlights the importance of understanding these psychological drivers in order to enhance marketing strategies and hotel management practices that align with growing consumer demand for environmentally responsible travel options. The paper argues that a positive attitude towards eco-friendly hotels can lead to increased customer satisfaction and loyalty, thereby providing competitive advantages to hotels that successfully implement sustainable practices. This study offers valuable insights into the dynamics of consumer behavior in the context of the hospitality industry's shift towards greater sustainability.